Grey directors, corporate governance and firms performance nexus: Evidence from Nigeria - Damilola Felix Eluyela; Abiola John Asaleye; Olabisi Rasheedat Popoola; Adedoyin Isola Lawal; Henry Egbezien Inegbedion (Cogent Economics & Finance, 2020)
There has been a consistent argument in the literature as regards the importance of grey directors on board, and their impact on firm performance with most studies focused on developed economies. However, little is known on the short and long-run implications. In this study, we examined the joint short-run and long-run causality relationship, as well as the long-run behaviour between grey directors and corporate performance of deposit money banks. Our sample includes 14 deposit money banks out of the 15 listed on Nigeria stock exchange for 2010-2017. The estimation techniques used include descriptive statistics, unit root test, panel co-integration test and fully modified ordinary least square regression (FMOLS). Using Tobin Q as the dependent variable, there is no flow of joint long-run causality from the independent variables. The significance of the short-run coefficients indicates joint causality moving from independent variable to the dependent variable in the short-run. Furthermore, the long-run equation shows a significant positive relationship between indigenous directors, the board size, non-executive directors and performance of the selected deposit money banks in Nigeria, while a negative correlation was observed with firm size. Grey director was insignificant in the long-run. The study concludes that aggregate policy changes need to carefully considered in promoting a long-term benefit and need to gear effort towards maximising the performance of the banking sector in the long-run through effective group decision.
Keywords: 330; causality; corporate governance; financial performance; grey directors